The Image of China in Milan Jovanović’s Tamo amo po istoku - Yuchao, Peng (Poznańskie Studia Slawistyczne, 2022)
Serbian traveler Milan Jovanović arrived in China in the 19th century, and after his return, his travelogue Tamo amo po istoku (Here and There in the East) was published. This article aims to reveal Jovanović’s perception of China in his writings, in order to analyze the image of China and more importantly, his dilemmas of self–positioning while facing the East and the West. By applying comparative literary imagery theory and cross–cultural methods, this paper interprets the literal value of Jovanović’s work, and discusses the interactions between the East and the West, as well as the “self” and the “others.” This article argues that Jovanović’s self–affirmation is faced with two “others”: the heterogenous “other” of Eurocentrism, and the homogenous “other” of Eastern utopia. His image of China is constructed in the tension between the two.